DERIVATION OF THE LORENTZ-EINSTEIN TRANSFORMATION VIA ONE OBSERVER (Journal of Engineering, 2010)
Lorentz-Einstein transformation derived by Einstein in his theory of special relativity. Physical laws and principles are invariant in all Galilean reference frames under this transformation. The transformation in every day use in a host of contexts as in free solution of the Dirac equation in the modern field of heavy ion in atomic physics. Most books on theoretical physics and special theory of relativity and all research papers have derived the Eorentz-Einstein transformation using various propositions and employing two observers each located in Galilean system with relative motion receding the same events in the space-time manifold. This paper derives Lorentz-Einstein transformation by proposing just one observer using local coordinates of two Galilean system with relative motion following the track of a spherical pulse of light, which to our knowledge is not found in the literature.